A new classification of HLA-DRB1 alleles based on acid–base properties of the amino acids located at positions 13, 70 and 71: impact on ACPA status or structural progression, and meta-analysis on 1235 patients with rheumatoid from two cohorts (ESPOIR and EAC cohort). Issue 1 (19th November 2015) - Ruyssen-Witrand, Adeline; van Steenbergen, Hanna W; van Heemst, Jurgen; Gourraud, Pierre-Antoine; Nigon, Delphine; Lukas, Cédric; Miceli-Richard, Corinne; Jamard, Bénédicte; Cambon-Thomsen, Anne; Cantagrel, Alain; Dieudé, Philippe; van der Helm-van Mil, Annette H M; et al.
Abstract : Objective: To group HLA-DRB1 alleles based on acid–base properties of amino acids at positions 13, 70 and 71 and analyse their association with the presence of anticitrullinated peptide antibodies (ACPA) and structural progression in 2 cohorts of early rheumatoid arthritis (RA). Methods: Patients with RA (N=612) from ESPOIR cohort and from EAC cohort (n=624) were genotyped for HLA-DRB1 alleles. The alleles containing the RAA sequence at positions 72–74 were classified into 3 groups according to the amino acid at positions 13, 70 and 71: BB encoding basic amino acids at positions 13, 70 and 71; A encoding acidic amino acids at positions 70 and 71; and BN encoding either neutral amino acids at position 13 and basic amino acids at positions 70 and 71, or basic amino acid at position 13 and neutral amino acids at positions 70 and 71. The associations between the different alleles and (1) the ACPA presence, and (2) the structural progression were assessed by χ 2 test; a meta-analysis was performed on the 2 cohorts using the Mantel-Haenszel method. Results: After meta-analysis, BB alleles were significantly associated with ACPA presence (OR (95% CI) 4.08 (3.14 to 5.31)) and structural progression (OR (95% CI) 2.33 (1.76 to 3.09)). The alleles protected significantly against ACPA presence (OR (95% CI) 0.37 (0.28 to 0.50)) and structural progression (OR (95% CI) 0.34 (0.23 to 0.50)). This acid–base classification allowed to separate another group BN with an intermediate risk of ACPA production (OR (95% CI) 1.14 (0.91 to 1.44)) and structural progression (OR (95% CI) 1.01 (0.77 to 1.33)). Conclusions: This new classification permitted to make a hierarchy of HLA-DRB1 alleles in terms of association with ACPA presence or structural progression in early RA.